Tumor Microenvironmental Competitive Endogenous RNA Network and Immune Cells Act as Robust Prognostic Predictor of Acute Myeloid Leukemia - Cheng, Yaqi; Wang, Xiaoran; Qi, Peiyan; Liu, Chengxiu; Wang, Shoubi; Wan, Qi; Liu, Yurun; Su, Yaru; Jin, Lin; Liu, Ying; Li, Chaoyang; Sang, Xuan; et al. (Frontiers in Oncology, 2021)
Acute myeloid leukemia (AML) is malignant hematologic tumors with frequentrecurrence and cause high mortality. Its fate is determined by abnormal intracellular competitive endogenous RNA (ceRNA) network and extracellular tumor microenvironment (TME). This study aims to build a ceRNA network related to AML TME to explore new prognostic and therapeutic targets. The RNA expression data of AML were obtained from the The Cancer Genome Atlas (TCGA) database. First, we used the ESTIMATE algorithm to calculate the immune cells and stromal cells infiltration scores in the TME and found that all scores were highly correlated with AML’s prognostic characteristics. Subsequently, differentially expressed mRNAs and lncRNAs between high and low score groups were identified to construct a TME-related ceRNA network. Further, the Cox-lasso survival model was employed to screen out the hub prognostic ceRNA network composed of 2 mRNAs (EPB41L3, COL2A1), 3 miRNAs (hsa-mir-26a-5p, hsa-mir-148b-3p, hsa-mir-148a-3p) and 2 lncRNAs (CYP1B1-AS1, C9orf106) and construct nomograms. Finally, we used CIBERSORT algorithm and Kaplan-Meier survival analysis to identify the prognostic TME immune cells and found that naive B cells, M2-type macrophages, and helper follicular T cells were related to prognosis, and the hub ceRNAs were highly correlated with immune cell infiltration. This study provided a new perspective to elucidate how TME regulates AML process, and put forward the new therapy strategies combining targeting tumor cells with disintegrating TME.